The Concept Of Innovation And The Process Of Innovation. Stages Of The Innovative Process. (Eurasian Journal of Humanities and Social Sciences, 2023)
The article covers methodological recommendations for increasing the understanding of teachers operating in secondary schools about the innovation and innovation process and the development of stages of the innovation process